Information, accountability and perceptions of public sector programme success: A conjoint experiment among bureaucrats in Africa. (7th May 2020) - Harris, Adam S.; Seim, Brigitte; Sigman, Rachel
Abstract: Motivation: Whether public sector organizations implement programmes successfully is a key concern of development scholars and practitioners across the world. While many studies purport the existence of a link between social accountability and public sector performance, this relationship has been difficult to study empirically. Purpose: This article examines whether bureaucrats expect public sector programmes with information‐sharing mechanisms, including visibility, transparency and collaboration, to be successful in terms of effectiveness and limiting corruption. Approach and Methods: The article uses a conjoint survey experiment administered to thousands of bureaucrats across three African countries: Ghana, Malawi and Uganda. By asking bureaucrats—those with insider knowledge of government programme operations—about two hypothetical programmes with randomly assigned characteristics, we examine whether bureaucrats associate opportunities for monitoring by citizens and civil society groups with the success of public sector programmes. Findings: Across diverse country and organizational contexts, bureaucrats consistently attribute high probabilities of success to programmes that are visible to the public, transparent in their implementation, and open to collaboration with civil society. Moreover, the inclusion of any one of these information‐sharing mechanisms can independently increase the perceived likelihood of success. The findings hold across institutional contexts and diverse subgroups of bureaucrats surveyed. Policy Implications: To promote success in the implementation of public sector development programmes, officials should look for ways to increase the visibility of their programmes, set requirements for frequent public updates on programme progress, and build in opportunities for outside groups to collaborate.